Exploration of the Function of Galactagogue in Fenugreek, Moringa, and Sauropus Androgynus Polyherbal Tea: Systematic Literature Review - Eva Kusumahati; Kintoko; Sagiran (Arbain Publishing, 2025)
This study aims to evaluate the effect of polyherbal tea consisting of fenugreek, Moringa oleifera, and Sauropus androgynus on breast milk production and quality, as well as the health of breastfeeding mothers. The method used was a Systematic Literature Review (SLR) based on PRISMA 2020, where studies were identified through a systematic search in the Scopus database using relevant keywords. Data were extracted from studies that met the inclusion criteria and were evaluated to determine the effectiveness and safety of polyherbal teas. The results showed that polyherbal tea supplementation has the potential to increase breast milk production by stimulating the hormones prolactin and oxytocin. Fenugreek and Moringa oleifera significantly increase milk production and change the nutritional profile of breast milk for the better, including increased unsaturated fatty acid content and antioxidant capacity. Sauropus androgynus leaves also show potential as galactogogues and maternal health supporters. In addition, this herbal supplementation provides additional benefits for maternal health, such as improved nutritional status and reduced fatigue. These findings are important because they provide stronger scientific evidence to support the use of herbal supplements in clinical practice, as well as suggesting that polyherbal teas can be an effective natural alternative in improving milk production and quality and supporting the health of breastfeeding mothers. Further research is needed to determine the optimal dosage and long-term effects of these herbal supplements, as well as to understand the synergistic interactions between the herbal ingredients. Relevant keywords for this study included: polyherbal tea, galactagogue, breast milk production, breast milk quality, fenugreek, Moringa oleifera, Sauropus androgynus, and breastfeeding maternal health.